2001
DOI: 10.1099/0022-1317-50-10-896
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and phenotypic characterisation of Borrelia burgdorferi sensu lato strains isolated from human blood

Abstract: Lyme borreliosis often presents initially with erythema migrans. Borreliae may disseminate from the primary skin lesion, and different organs and systems could be affected. Borrelia strains were isolated from blood of 70 patients with Lyme borreliosis, including 10 patients from whom borreliae were also isolated from skin. The aim of the present study was to characterise the isolates with regard to their phenotypic and genotypic characteristics. Borreliae were cultivated in MKP medium. Species identification a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
114
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(124 citation statements)
references
References 0 publications
6
114
0
4
Order By: Relevance
“…Skin and CSF were inoculated into modified Kelly-Pettenkofer medium immediately after they were obtained from patients (33,35). Citrated blood samples were transported to the laboratory where they were processed, and only plasma was inoculated in modified Kelly-Pettenkofer medium (34). All the samples were incubated at 33°C and checked for the presence of borreliae weekly (27).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin and CSF were inoculated into modified Kelly-Pettenkofer medium immediately after they were obtained from patients (33,35). Citrated blood samples were transported to the laboratory where they were processed, and only plasma was inoculated in modified Kelly-Pettenkofer medium (34). All the samples were incubated at 33°C and checked for the presence of borreliae weekly (27).…”
Section: Methodsmentioning
confidence: 99%
“…), ticks, and reservoir hosts (9,17,25,29,42,49) obtained worldwide have been analyzed by many different phenotypic methods, such as well-established protein profile and serotyping system based on the heterogeneity of OspA and OspC proteins (33)(34)(35)(42)(43)(44)(45), and several genotypic approaches (42). Analysis of borrelial chromosomal or plasmid DNA, as performed by genotypic methods, provides more precise information on the genetic relationships among Borrelia strains (2, 5, 7, 22, 33-35, 42, 47).…”
mentioning
confidence: 99%
“…However, some differences in the region of 20-25 kDa proteins (presumably OspC) were observed. Considerable antigenic variations have been documented for Borrelia strains; besides the adaptive mechanisms of the spirochetes that influence protein expression, each strain has its own potential to express a particular protein (Wilske et al 1996, Ruzic-Sabljic et al 2001). According to these results, the antigen obtained could be used in a Western-blot for the diagnosis of Lyme borreliosis in humans.…”
mentioning
confidence: 99%
“…Molecular analyses such as protein and plasmid profiles, reactivity with monoclonal antibodies, DNA-DNA relatedness, 16 rRNA, flagellin and ospA gene sequence analyses, and finally multilocus enzyme electrophoresis demonstrated that these B. burgdorferi isolates are phenotypically and genotypically divergent (11,12,28,35,38,40). These studies also established that all isolates are gathered in several species and genomic groups that include B. burgdorferi sensu stricto, B. garinii, B. afzelii, B. japonica, B. andersonii, B. valaisiana, B. lusitaniae, B. tanukii, B. turdi, B. bissettii, and B. sinica species (3,13,21,26,33).…”
mentioning
confidence: 99%